The influence of different hand paddle size on 100-m front crawl kinematics - Lopez-Plaza, D.; Alacid, F.; Lopez-Minarro, P. A.; Muyor, J. M. (Journal of Human Kinetics, 2012)
The purpose of this study was to determine the influence of different sizes of hand paddles on kinematic parameters during a 100 m freestyle swimming performance in elite swimmers. Nine elite swimmers (19.1 ± 1.9 years) completed three tests of 100 m without paddles, with small paddles (271.27 cm2) and with large paddles (332.67 cm2), respectively. One video camera was used to record the performance during the three trials. The mean swimming velocity, stroke rate and stroke length were measured in the central 10 meters of each 50 m length. The results showed that stroke length tended to increase significantly when wearing hand paddles (p < 0.05) during both the first and second 50 m sections whereas the increase in swimming velocity occurred only in the second 50 m (p < 0.05). Conversely, the stroke rate showed a slight decreasing trend with increasing paddle size. During the 100 m freestyle trial the stroke kinematics were changed significantly as a result of the increase in propelling surface size when hand paddles were worn.